Períodos de interferência das plantas daninhas em duas variedades de mandioca no sistema de plantio direto - Moratelli, Gustavo (2017)
The economic factors that determine the profitability of cassava producers such as weed control cost and the monetary value of the roots or their industrialized derivatives can be used to determine the acceptable period of weed interference before the control decision . Thus, the objective of the present work will be to determine the period prior to interference (PAI) and the period before the damage to the economic yield (PADRE) caused by interference of weeds in two varieties of cassava in the first cycle of the crop. Planting was carried out in a no - tillage system, with a randomized complete block design in a 2 x 11 factorial scheme, two varieties in eleven weed cohabitation periods and four replications. In the plots were allocated the 'Baianinha' and 'Clone 56-03' varieties. The experiment was conducted in only one crop cycle (year 2015/16 - 1st cycle of cultivation / 10 months). The growing periods of weed cohabitation with the crop were; 20, 40, 60, 80, 100, 120, 140, 160, 180, 200 and 220 days after planting. Plots were kept totally free from weed cohabitation (weed control) and others kept in common with weeds (control coexistence) until harvest. The characterization of the weed community at the end of each coexistence period will be done using the square of inventory method, using tables of 0.25 m2, randomly placed in each plot. Both varieties were evaluated: plant height, leaf area, number of roots, harvest index, root productivity and starch content. The means were submitted to statistical analysis of regression, being the equations chosen based on the significant models, approved in the test of normality, biological logic and high R², using the computer program SigmaPlot 12.0. The PAI obtained by the Clone 56-03 variety was 87 DAP for root production and 79 DAP for starch production. The PAI obtained by the Baianinha variety was 30 DAP for root production and 27 DAP for starch production. Approaching the average price paid by the roots to the producers in the year 2016, with the control cost low the PADRE for Clone 56-03 was 30 DAP, with the high control cost was 75 DAP. For Baianinha the PADRE with low control cost was 14 DAP, with the high control cost was 35 DAP. For starch production the Clone PADRE 56-03 was 18 DAP for low control cost and 44 DAP for high control cost. Baianinha presented 7 DAP for low control cost and 44 DAP for high weed control cost.